2019
DOI: 10.3389/fpls.2019.00152
|View full text |Cite
|
Sign up to set email alerts
|

Phytochrome A Regulates Carbon Flux in Dark Grown Tomato Seedlings

Abstract: Phytochromes comprise a small family of photoreceptors with which plants gather environmental information that they use to make developmental decisions, from germination to photomorphogenesis to fruit development. Most phytochromes are activated by red light and de-activated by far-red light, but phytochrome A (phyA) is responsive to both and plays an important role during the well-studied transition of seedlings from dark to light growth. The role of phytochromes during skotomorphogenesis (dark development) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Deficiency of SlPHYA leads to reduced photosynthetic electron transport rates, lower levels of starch in vegetative tissues and impaired shoot biomass accumulation (Kharshiing and Sinha 2016). SlPHYA is also responsible for the control of carbon flux related processes, especially in dark-grown seedlings, optimizing growth rate and biomass partitioning according to the light availability (Carlson et al 2019). SlPHYB1 is mainly expressed in vegetative tissues and SlPHYB2, in the fruit pericarp (Hauser et al 1997;Bianchetti et al 2017), and therefore, their impacts on the productivity must be analyzed throughout the tomato life cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Deficiency of SlPHYA leads to reduced photosynthetic electron transport rates, lower levels of starch in vegetative tissues and impaired shoot biomass accumulation (Kharshiing and Sinha 2016). SlPHYA is also responsible for the control of carbon flux related processes, especially in dark-grown seedlings, optimizing growth rate and biomass partitioning according to the light availability (Carlson et al 2019). SlPHYB1 is mainly expressed in vegetative tissues and SlPHYB2, in the fruit pericarp (Hauser et al 1997;Bianchetti et al 2017), and therefore, their impacts on the productivity must be analyzed throughout the tomato life cycle.…”
Section: Introductionmentioning
confidence: 99%
“…The data suggests a slow breakdown of storage protein in the fri mutant 57 and it could be an indication of the absence of light-dependent development in phytochrome mutant as PhyA is the primary photoreceptor responsible for perceiving and mediating various responses to FR light 68 70 . In control seedling, most of the sugars are consumed after 96 h, under FR.…”
Section: Resultsmentioning
confidence: 92%
“…Carlson et al . 57 investigated the transcriptomic and gel-based proteomic profile of tomato seedlings during the transition from dark to light (red light) and found that PhyA regulates carbon flux through major primary metabolic pathways. A study by Fox et al .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it has been extensively reported that activated PHYs induce post-translational changes in PIF proteins, including sequestration, phosphorylation, polyubiquitylation, and subsequent degradation through the 26S proteasome-mediated pathway 3 . Although the effect of light on plant phenotypes and the plant transcriptome has been studied for decades [9][10][11] , the involvement of epigenetic regulatory mechanisms in light-dependent changes in the transcriptional landscape remains poorly addressed.…”
Section: Introductionmentioning
confidence: 99%